THE EFFECT OF DISTRIBUTIVE JUSTICE, PROCEDURAL JUSTICE AND INTERACTIONAL JUSTICE ON JOB SATISFACTION AND ITS IMPACT TOWARD HONORARY EMPLOYEE ORGANIZATIONAL COMMITMENT AT FACULTY OF ECONOMICS, TANJUNGPURA UNIVERSITY - B2042141023, HASANUDIN (Equator Journal of Management and Entrepreneurship (EJME), 2016)
This research was conducted in order to determine whether distributive justice, procedural justice and interactional justice has positive effect on job satisfaction and its impact on organizational commitment in honorary employees at Faculty of Economics, Tanjungpura University. The population in this study is 34 honorary employees of faculty of Economics, University of Tanjungpura. Samples were obtained as much as 34 respondents. The type of research is quantitative research with survey approach, by using path analysis as analysis tools. Based on the result analysis, it is found that distributive justice, procedural justice and interactional justice has positive effect on honorary employee job satisfaction at Faculty of Economics, University Tanjungpura. The result also can be interpreted that if distributive justice, procedural justice and interactional justice increase, job satisfaction will be increases as well. Distributive justice, procedural justice and interactional justice positively affects on organizational commitment of honorary employees at Faculty of Economics, Tanjungpura University. This means that if the distributive justice, procedural justice and interactional justice increase, organizational commitment will be increase as well. Job satisfaction has significant positive effect on employee organizational commitment of honorary employee at Faculty of Economics, Tanjungpura University. This means that if job satisfaction increases, organizational commitment will be increase as well. Keywords : Â Distributive Justice, Procedural Justice, Interactional Justice, Job Satisfaction, Organizational Commitment